Lesotho Policy Notes - World Bank (World Bank, Washington, DC, 2020)
This policy notes seek to distill key findings from a broad range of World Bank Group engagements in Lesotho, including policy dialogue, analytical work, strategic documents, project lending, and trust funded activities. It builds on discussions with government counterparts, development partners, non-governmental organizations, representatives of the private sector, and other stakeholders. The policy note includes synopses on each topic, highlighting key issues and challenges, and concluding with actionable policy recommendations. It covers a broad range of policy issues but are not intended to be comprehensive or exhaustive. The policy notes start with the overview of the World Bank program and structured under five broad thematic groupings. It begins with key issues and challenges, and unmaterialized opportunities. The first part is reflected in policy measures in both short term and medium to long term.